Penyematan Fonem Vokal pada Gairaigo di Album Traveler Karya Official髭男dism (Higedan) - Paradida, Yulia Putri; Luhulima, Fiona Djunita Natalia; Tarigan, Marsten Lihardo (Japanese Literature Study Program, Faculty of Letters, Dr. Soetomo University, 2023)
The purpose of this study is to identify the embedding of the vocal phoneme in gairaigo in Higedan’s Japanese song lyrics and to describe the changes in moral and its syllables. The benefit of this research is that Japanese language learners can understand the detailed process of the vocal embedding in gairaigo in Japanese song lyrics. The theories used are Hirayama’s theory about vowel phonemes in Japanese, Kawarazaki and Kubozono’s theory about embedding vowel phonemes in closed syllables, and changing the syllables in gairaigo, Sutedi’s theory about mora and syllables. This research method is a qualitative method with a descriptive approach. The data source is from the album song Traveler by the Japanese band Official Hige Dandism (Higedan) with data in the form of gairaigo which has undergone a process of embedding vocals. Researchers used literature study techniques to collect data, then analyzed with descriptive techniques. The findings found that gairaigo underwent a process of embedding vowels as many as 15 words which were divided into 3. First, embedding vowel phonemes at the beginning of words as many as 5 words, namely furiidamu (フリーダム), adobanteeji (アドバンテージ), sutookaa (ストーカー), kurosuwaado (クロスワード ) and sutoorii (ストーリー ). Second, the embedding of vowel phonemes in the middle of the word consists of 2 words, namely, iesutadai (イエスタデイ) and kontorooru (コントロール). Third, embedding vowel phonemes at the end of words as many as 8 words namely, poketto (ポケット), patto (パット), binteeji (ビンテージ), endo (エンド), fitto (フィット), taaminaru (ターミナル), rokku (ロック), and souru (ソウル). The process of embedding these vocal phonemes also influences the occurrence of changes in mora and syllables. Keywords: gairago; Higedan song lyrics; vocal embedding; vowel phoneme.